Tourism development in Madeira: an analysis based on the life cycle approach - Almeida, António (2020)
This paper identifies Madeira Island’s growth stage in accordance with Butler’s life cycle model. Life cycle analysis is pursued using an econometric approach over an extended period, from 1976 to 2006. The results suggest that Madeira is about to enter the stagnation phase. The industry’s development since the 1970s was found to conform to Butler’s model, but in its own way. In the case of Madeira, the island’s positive image and the time span within each of the life cycle stages challenge the traditional life cycle model, suggesting rather that the maturity stage may persist indefinitely.